42.9k views
1 vote
Given: ΔABC Prove: m∠ZAB = m∠ACB + m∠CBA We start with triangle ABC and see that angle ZAB is an exterior angle created by the extension of side AC. Angles ZAB and CAB are a linear pair by definition. We know that m∠ZAB + m∠CAB = 180° by the . We also know m∠CAB + m∠ACB + m∠CBA = 180° because . Using substitution, we have m∠ZAB + m∠CAB = m∠CAB + m∠ACB + m∠CBA. Therefore, we conclude m∠ZAB = m∠ACB + m∠CBA using the .

User Smk
by
5.6k points

1 Answer

2 votes

Answer:

We know that m∠ZAB + m∠CAB = 180° by the

✔ angle addition postulate

.

We also know m∠CAB + m∠ACB + m∠CBA = 180° because

✔ of the triangle angle sum theorem.

Using substitution, we have m∠ZAB + m∠CAB = m∠CAB + m∠ACB + m∠CBA.

Therefore, we conclude m∠ZAB = m∠ACB + m∠CBA using the

✔ subtraction property

.

Explanation:

i did it on edge 2020

User Shaunsephton
by
5.5k points